The effect of overgeneral autobiographical memory retrieval on rumination - Raes, F; Hermans, D; Williams, J; Geypen, L; Eelen, P (2006)
From distinct research traditions rumination and overgeneral autobiographical memory retrieval (OGM) have emerged as two vulnerability markers for depression and depressive relapse (Nolen-Hoeksema, 2004; Williams, 2004). Recent research further suggests a causal relation between rumination and OGM (e.g., Watkins and Teasdale, 2001). The present study investigated the inverse relationship, that is, OGM causally influencing ruminative thinking. A scrambled sentences procedure was used to assess the extent to which 112 student participants were engaged in a mental mode consistent with ruminative thinking following either a specific or overgeneral memory retrieval style manipulation. Trait rumination was also assessed prior to the experimental retrieval manipulation, using a self-report scale. It was found that high ruminators, following an overgeneral (as compared to a specific) retrieval style, unscrambled sentences relatively more into sentences with a ruminative meaning. In non or low ruminators this retrieval style manipulation had no such effect. Alongside the findings of Watkins and colleagues (e.g., Watkins and Teasdale, 2001), the present results are consistent with the view of rumination and OGM as two mutually reinforcing vulnerability factors for depression (Williams, 1996, 2004).